Motivational Disposition in English Writing Skills Development for EFL Pre-service Teachers: A Comparative Pilot Study of Myanmar and Hungary - Maung, Ei Phyoe; Gyori, János Gordon; Kálmán, Csaba (GILE Journal of Skills Development, 2025)
Developing strong writing skills is essential for EFL pre-service teachers’ career readiness and professional development especially in the age of artificial intelligence (AI). Myanmar and Hungary's English language teacher training programmes share similarities in practicum, course content, aims, assessment, and professional development initiatives, but differ in class and group sizes, and governmental initiatives in second language (L2) research. Their shared emphasis on English teacher training despite their distinct educational contexts brought the researchers to conduct this comparative pilot study. Despite extensive L2 motivation research in English language teaching (ELT), the motivational disposition of EFL pre-service teachers in English writing remains unexplored in both countries. Current English teacher training programmes in both contexts emphasise quality teaching for academic achievement, particularly in English writing. This study addresses this gap and its implications for skills development and employability, by presenting results from a quantitative questionnaire study, focusing on the process writing approach. The study aims to assess the reliability of the pilot questionnaire developed by the researchers, explore pre-service teachers’ motivational disposition in English writing, and identify dimensions contributing most to motivated learning behaviour. Statistical analyses, including Cronbach’s alpha and linear regression, were conducted, revealing differences in motivators between Myanmar and Hungarian participants. The study concludes with recommendations for enhancing intrinsic motivation in Myanmar and emphasising ideal L2 selves in Hungary to improve EFL pre-service teachers’ motivated learning behaviour and writing performance. These insights also contribute to strengthening teacher training practices, fostering sustainable careers, and equipping pre-service teachers with critical skills that are crucial for their educational and professional success in the long run.